Tree integration in conservation agriculture: A case study of teak (Tectona grandis) + bael (Aegle marmelos) based agroforestry in the Bundelkhand region - RAM, ASHA; SAMADHIYA, ANIRUDH; KUMAR, NARESH; DEV, INDER; DEBNATH, SOVAN; SINGH, RAMESH; YADAV, ASHOK; SINGH, PRIYANKA; PANDEY, SANTOSH; ANURAGI, H; HANDA, A K; ARUNACHALAM, A (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during the winter (rabi) seasons of 2021–22 and 2022–23 at ICAR-Central Agroforestry Research Institute, Jhansi, Uttar Pradesh to study the impact of conservation agriculture practices within a teak (Tectona grandis L.) + bael (Aegle marmelos L.)-based agroforestry system on growth rate and yield parameters of tree and crop component, as well as on soil properties. It examined the effect of tillage methods and residue retention on the growth and yield of chickpea (Cicer arietinum L.) and linseed (Linum usitatissimum L.) as well as soil properties. The experiment was laid out in a randomized block design (RBD), with three replications having eight treatments of comprising combinations, viz. Tillage methods (conventional and minimum); Cropping systems (sorghum-chickpea and maize-linseed); and Residue management practices (residue retention and no retention). Results indicated that residue retention under conventional tillage significantly enhanced plant height and dry matter accumulation in both linseed and chickpea. Crop yields were comparable under conventional and minimum tillage, although residue retention significantly boosted the yields of both crops. Conservation agricultural practices contributed to higher productivity in the teak + bael-based agroforestry system. Residue retention improved soil organic carbon content by 24–39% compared to no residue retention. Additionally, nutrient availability (N, P, K, S, Zn, Fe, Mn, and Cu) was enhanced through minimum tillage combined with residue retention.